2012
DOI: 10.1007/s00268-012-1716-8
|View full text |Cite
|
Sign up to set email alerts
|

Periampullary Diverticulum May Be an Important Factor for the Occurrence and Recurrence of Bile Duct Stones

Abstract: There is a close correlation between PAD and the formation of biliary tract stones. A particularly close correlation was found between PAD and choledocholithiasis after cholecystectomy. PAD may be an important risk factor for the occurrence or recurrence of biliary tract stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 24 publications
6
47
0
Order By: Relevance
“…PD has been reported to be a risk factor for development of CBDS, while intra-diverticular overgrowth of bacteria and bile flow disturbance are also believed to increase its incidence 21 22. As noted in those studies, clinical presence of PD is thought to be a risk factor and the hazard ratio was 1.873 in the current COX proportional hazard model findings, thus we cannot deny that possibility.…”
Section: Discussionmentioning
confidence: 50%
“…PD has been reported to be a risk factor for development of CBDS, while intra-diverticular overgrowth of bacteria and bile flow disturbance are also believed to increase its incidence 21 22. As noted in those studies, clinical presence of PD is thought to be a risk factor and the hazard ratio was 1.873 in the current COX proportional hazard model findings, thus we cannot deny that possibility.…”
Section: Discussionmentioning
confidence: 50%
“…After the introduction of three types of PAD according to the position of the major papilla in endoscopic examination, these types have become generally accepted for the classification of PAD. In the aspect of size, large and small PAD were suggested by a diameter cut‐off of 15 or 20 mm …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have concluded that a diameter of either 1.5 or 2.0 cm should be used to classify small and large PAD. 2,6 PAD originates at weak areas in the duodenal wall, which include perivascular connective tissue sheath pathways and the entrances of the common bile duct (CBD) and pancreatic duct. 7 It has been previously shown that increasing age leads to increase in prevalence of PAD.…”
Section: Introductionmentioning
confidence: 99%